Analysis of hemocytes in Lymnaea stagnalis: Characterization and effects of repeated hemolymph collections. (October 2016) - Boisseaux, Paul; Delignette-Muller, Marie-Laure; Abbaci, Khédidja; Thomas, Hélène; Garric, Jeanne
Abstract: The first part of the study was devoted to test the hypothesis according to which the hemolymph of Lymnaea stagnalis can be collected repeatedly – regardless the time-intervals – at an individual scale without impact on survival nor immunocapacity defined as the hemocyte density and viability. No significant effects on snail survival were observed when repeated hemolymph samplings were performed at frequencies ranging from 96 h up to 24 h. The frequency of hemolymph sampling had no significant effects on hemocyte density but the hemocyte viability was slightly increased for the 24 h frequency group. Hence, we recommend setting the frequency lower than 48 h after two consecutive samplings for further assessment of hemocyte density and viability. Furthermore, a slight "day" effect was observed on snail immunocapacity. These results support the idea that L . stagnalis is a promising gastropod model in environmental immunotoxicology. A time-course analysis of individual hemocytes parameters can be evaluated with a relative confidence in the non-detrimental effect of the sampling. Linear mixed-effect models allow taking the "day" effect into account and so the possible effect of an environmental factor (i.e. xenobiotic exposures) can be analyzed. Statistical inferences indicated that the inter-individual variability for these hemocyte endpoints were on the same order of magnitude than intra-individual variability. The second part of the study was devoted to provide greater insights into the structure/ultrastructure of hemocytes in L . stagnalis . Only one type of hemocyte has been observed. The hemocytes in their free-floating status showed ovoid or spherical shapes. Some hemocytes exerted filopodia and structures shaped like sailboats. Their ultrastructure showed signs of intense cellular activity. Two peculiar organelles were observed. One corresponds to a massive perinuclear structure of dense aspect. The other corresponds to a structure with fibrillary arrangements. These two structures deserve further investigation in order to understand their nature, function and importance in the snails' immunocompetence. Graphical abstract: Highlights: Snail survival was not significantly affected by the frequency of mechanical hemolymph collections (from 24 h to 96 h). Under repeated collections, hemocyte density and viability was independent of the sampling frequency, except at 24 h. Over two consecutive hemolymph collections, we recommend increasing time interval to higher than 48 h. Hemocyte ultrastructures have revealed two peculiar organelles that deserve further researches.